2000
DOI: 10.1677/joe.0.1650509
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide but not other sulphonylureas stimulates release of neuropeptide Y from perifused rat islets and hamster insulinoma cells

Abstract: We have studied the effects of first and second generation sulphonylureas on the release of insulin and neuropeptide tyrosine (NPY) from hamster insulinoma tumour (HIT-T15) cells and isolated rat islets. In the presence of 5·5 mmol/l glucose all sulphonylureas stimulated insulin release from the HIT cells (P<0·01 ANOVA, nd4) but only glibenclamide (GLIB, 10 µmol/l) stimulated the release of NPY (mean ... control 11·1 1·3 vs GLIB 28·4 4·1 fmol/h per 10 6 cells, P<0001, n=16). In isolated perifused rat islets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Similarly, it has been reported that chronic treatment with sulphonylureas such as glibenclamide leads to a decline in their insulin-tropic activity due to a seconder failure in increasing insulin secretion such as ␤-cell exhaustion or desensitisation to glucose (Kulkarni et al, 2000;Ball et al, 2004). In this study, the progressive reduction in the blood glucose levels of alloxan-diabetic rabbits might be due to a cumulative action of the extract during the period of treatment and also associated with an increase in the blood insulin levels.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, it has been reported that chronic treatment with sulphonylureas such as glibenclamide leads to a decline in their insulin-tropic activity due to a seconder failure in increasing insulin secretion such as ␤-cell exhaustion or desensitisation to glucose (Kulkarni et al, 2000;Ball et al, 2004). In this study, the progressive reduction in the blood glucose levels of alloxan-diabetic rabbits might be due to a cumulative action of the extract during the period of treatment and also associated with an increase in the blood insulin levels.…”
Section: Discussionmentioning
confidence: 96%
“…*p < 0.05 and **p < 0.001 denotes significant differences from the corresponding control. and Filipponi et al, 1983;Kulkarni et al, 2000;Patane et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the viability of the tissue was verified by a 45-min exposure to 56 mmol/l KCl. α-Melanocyte–stimulating hormone (α-MSH), cocaine and amphetamine–regulated transcript, thyrotropin-releasing hormone, corticotrophin-releasing hormone, neuropeptide Y, and agouti-related peptide (AgRP) in the aCSF were measured using established radioimmunoassay (22,3034). …”
Section: Methodsmentioning
confidence: 99%